Writings on political economy. - Quinn, Michael 1961-; Bentham, Jeremy 1748-1832 (Bentham, Jeremy 1748-1832. Works. 1968., 2016)
"In the mid-1780s Bentham drafted his first sustained discussions of political economy and public finance for Projet Matiáere (itself part of Projet d'un corps de loix complet). Those discussions are now lost, but the corresponding marginal contents open this volume, followed by three closely related appendices. The volume continues with Defence of Usury, first published 1787, which was well received, quickly translated, and established some reputation for Bentham in political economy. In 1790, whilst preparing a second edition, Bentham drafted the raft of additional materials included here in five appendices. At the same time he began Manual of Political Economy, an introductory handbook which he never finished, while the surviving text appears here, supplemented by seven appendices. In March 1793 Bentham reacted to press reports of the Irish Budget by composing A Protest against Law Taxes, a trenchant critique of the taxation of legal proceedings, and the denial of justice to the poor, which was printed in 1793, published in 1795, and extended in 1816, and which completes the volume." -- Publisher's description